Analysis of The Systhematic Literature Review Related to Electronic Teaching and Learning of Arabic for Non-Native Speakers: Analisis Tinjauan Literatur Sistematik Berkaitan Reka Bentuk Pengajaran dan Pembelajaran Elektronik Bahasa Arab untuk Bukan Penutur Jati - Asmuzi, Noor Faridawati; Mohamed, Yuslina; Ismail, Sulaiman (Jurnal Pendidikan Bitara UPSI, 2022)
This study will discuss the literature review related to electronic teaching and learning of Arabic for non-native speakers in previous studies and integrate the findings of previous studies to explore new issues to be studied. The use of e-learning covers non-native speaker students in primary, secondary and university schools. Data was obtained through a qualitative method that applied a document analysis design based on a systematic literature review (SLR) as a foundation. Each topic will be discussed in detail to get a comprehensive picture related to this e-learning used in teaching and learning Arabic Language. The results of the study show that there are various designs that are suitable for the electronic teaching of Arabic in past studies. It covers four language skills; namely Listening and Speaking, Reading and Writing as well as Arabic Grammar and Morphology skills. Developers need to be creative and smart in choosing programs in the preparation of Arabic e-learning designs in order to achieve the targeted objectives. The concept of asynchronous e-learning for the enrichment of Arabic vocabulary, grammar and morphology skills is more preferred by scholars because it applies the concept of self-learning. Students can master the learning after the physical learning and as a reinforcement of skill mastery. Findings also show that problems arising from previous studies related to student motivation and interest can be overcome because the elements found in electronic design can stimulate the curiosity and enthusiasm of users in learning Arabic. Therefore, the study of synchronous and asynchronous e-learning for non-native Arabic speakers is necessary and appropriate to develop.